1972
DOI: 10.1111/j.1537-2995.1972.tb04452.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Joa: An Antibody Defining a High‐frequency Erythrocyte Antigen

Abstract: A "new" antibody, named anti-Joa, defining a high-frequency erythrocyte antigen has been found in the sera of two Negro patients. The two bloods are mutually compatible but a large number of other erythrocyte samples lacking common antigens are Jo(a+). A sibling of one patient is Jo(a+) but no other family studies were possible.Anti-Joa reacted with 3,000 group 0 but otherwise unselected blood samples, mostly from Caucasians, and with 768 blood samples from Negroes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…The high‐prevalence antigen Jo a 12 was shown to have a phenotypic association with Gy a and Hy antigens because RBCs with either the Gy(a–) phenotype or the Hy– phenotype are also Jo(a–) 13,14 . Another high‐incidence antigen, Jc a , was shown to be associated with Gy a and Hy 15 but later shown not to be a discrete antigen 16,17 …”
Section: Characteristics Of Dombrock As Revealed By Hemagglutinationmentioning
confidence: 99%
“…The high‐prevalence antigen Jo a 12 was shown to have a phenotypic association with Gy a and Hy antigens because RBCs with either the Gy(a–) phenotype or the Hy– phenotype are also Jo(a–) 13,14 . Another high‐incidence antigen, Jc a , was shown to be associated with Gy a and Hy 15 but later shown not to be a discrete antigen 16,17 …”
Section: Characteristics Of Dombrock As Revealed By Hemagglutinationmentioning
confidence: 99%
“…Anti -Jo a (Joseph) was fi rst described when cells and sera of two African American patients with antibodies to high frequency antigens were found to be mutually compatible [38] , though subsequent genotyping suggests that the eponymous antibody may actually have been anti -Hy [37] . Another example of anti -Jo a was found in an African American sickle cell disease patient [39] , though he was also subsequently found to have an unexpected genotype, being heterozygous for the DO * JO allele and a normal DO * B allele [37] .…”
Section: Gy a ( Do3) And Gy( A−) The Do Null Phenotypementioning
confidence: 99%
“…Do a , Do b , and Jo a are fully expressed on cord red cells [11,12,38,40] . In contrast, it is reported that Gy a and Hy are expressed only weakly on cord cells [27,34] .…”
Section: Development and Distribution Of Dombrock Antigensmentioning
confidence: 99%
“…Anti‐Jo a (Joseph) was first described in 1972 and was discovered when an antibody in the serum of two unrelated black individuals was mutually compatible 1 . This antibody was incompatible with all other RBCs tested, and the Jo a antigen was described as an independent high‐incidence antigen.…”
mentioning
confidence: 99%